The Value of Firm Networks: A Natural Experiment on Board Connections - Faia, Ester; Mayer, Maximilian; Pezone, Vincenzo (The Review of Corporate Finance Studies, 2026)
We present causal evidence on the effect of boardroom networks on firm value. We exploit a ban on interlocking directorates of Italian financial and insurance companies as exogenous variation and show that firms that lose centrality in the network experience negative abnormal returns around the announcement date. The key driver of our results is the role of boardroom connections in reducing asymmetric information. We find stronger effects for firms with fewer business partners and less experienced directors. Finally, we show that network centrality has a positive effect on directors’ compensation, providing evidence of rent sharing, and liquidity. (JEL: D57, G14, G32, L14) Received: 25 January 2024Editor: Andrew EllulAuthors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.